PALLADIUM(II) CHLORIDE COMPLEXATION: SPECTROPHOTOMETRIC INVESTIGATION IN AQUEOUS SOLUTIONS FROM 5 TO 125°C AND THEORETICAL INSIGHT INTO PD-CL AND PD-OH2 INTERACTIONS - Boily J.F.; Seward T.M. (My University, 2005)
Monomeric palladium(II) chloro aqua complexes of the form PdClr(H2O)4-r2-r (r = [0,4]) were studied both experimentally and theoretically to gain insight on both the stabilities and the nature of palladium-chloride interactions.The thermodynamic stabilities of these complexes were studied in aqueous solutions from 5 to 125°C with UV-vis spectrophotometry using a quartz flow-through cell. Tentative measurements up to 200°C were also carried out in pressurised titanium and gold-lined optical cells but revealed important losses in soluble palladium. The strong ligand-to-metal charge transfer bands of the palladium complexes below 350 nm were used to constrain the stepwise thermodynamic formation constants at each temperature, using results of singular value decompositions of the spectra over a broad range of palladium:chloride ratios and wavelengths. The temperature-dependent constants were used to obtain changes in enthalpy and in entropy for each reaction. The thermodynamic stabilities of PdCl(H2O)3+, PdCl2(H2O)20, and PdCl3(H2O)- are larger at higher temperatures, whilst the one of PdCl42- is smaller. All changes in entropies are positive for the former three species, but negative for the latter, presumably due to a larger solvent reorganisation around the doubly charged PdCl42- species. The room temperature thermodynamic values derived from this study are also in agreement with previously published calorimetric data.Theoretical calculations on the intramolecular distributions of electrons in the different palladium(II) chloro aqua complexes, using the methods of atoms in molecules and of the electron localisation function, showed Pd-Cl and Pd-OH2 interactions to be of largely closed-shell/ionic nature. These interactions induce an important distortion of the outer core shell electrons of Pd, as well as stable accumulations of electrons between adjacent Pd-Cl and Pd-OH2 bonds known as ligand opposed core charge concentrations.